2014
DOI: 10.1007/s11160-014-9378-2
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic diet changes and food partitioning of Haemulon spp. coral reef fishes, with a review of the genus diet

Abstract: The genus Haemulon contains some of the most abundant and ecologically important reef fishes in the South Atlantic Ocean. However, their life history attributes have not been widely studied. Knowledge of ontogenetic changes in their resource use is critical to understanding the processes structuring natural communities. The present study analysed ontogenetic diet changes and food partitioning in Haemulon spp. We collected stomach contents from 276 individuals of four different size classes from four sympatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 70 publications
(80 reference statements)
2
20
0
Order By: Relevance
“…family, assuming that closely‐related prey have similar morphological and behavioural characteristics and therefore provide similar dietary choices. These studies have shown that the taxonomic composition of the prey of a fish species frequently changes as that predator increases in size (French et al ., ; Pereira et al ., ; Coulson et al ., ) and can differ among habitats and regions (Platell et al ., ; French et al ., ) and season (Fanelli et al ., ; Schückel et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…family, assuming that closely‐related prey have similar morphological and behavioural characteristics and therefore provide similar dietary choices. These studies have shown that the taxonomic composition of the prey of a fish species frequently changes as that predator increases in size (French et al ., ; Pereira et al ., ; Coulson et al ., ) and can differ among habitats and regions (Platell et al ., ; French et al ., ) and season (Fanelli et al ., ; Schückel et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…However between the 2 species, there is a resource partitioning in terms of the proportion and frequency of prey items. These changes are probably a consequence of habitat use and morphological changes in the fish (Ward-Campbell et al 2005, Russo et al 2008, Pereira et al 2014, which results in a wide trophic spectrum (generalist) or reduced trophic spectrum (specialist) (Hammerschlag et al 2010). These variations are in accordance with the niche partitioning theory (Bolnick et al 2003, Mariani et al 2011, which states that every time that a species decreases food resources shared by specialization, it reduces interspecific competition, while intraspecific competition increases (Pereira et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, E. argenteus and E. gula had a similar diet, however a food resource partition was observed, where E. argenteus fed on amphipods and E. gula on annelids. This flexibility of diet, could be influenced by several factors including salinity, dissolved oxygen, temperature (Dantas et al 2013), prey distribution (Pech et al 2007, Kuk-Dzul et al 2012, morphological changes such as increased mouth size (Ward-Campbell et al 2005, Nakane et al 2011, strengthening of the jaw and teeth, an increase in capturability (Nanjo et al 2008, Pereira et al 2014, or a simple change in metabolic requirements (Wootton 1998, Hammerschlag et al 2010 where juveniles use the energy for growth and survival, while adults utilize it for reproduction and maintenance (Gning et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reconstruction of food webs to sufficient taxonomic levels has been challenging because of the high species richness involved in trophic interactions and the complex three-dimensional structure in which these interactions occur (Enochs & Glynn, 2017). The vast majority of studies using morphological classification of semi-digested food remains in gut contents concluded that coral reef associated taxa within feeding guilds (e.g., browsing herbivores, invertivores, or planktivores) had widely overlapping diets (Anderson et al, 1981;Bouchonnavaro, 1986;Depczynski & Bellwood, 2003;Gladfelter & Johnson, 1983;Harmelin-Vivien, 1979;Hiatt & Strasburg, 1960;Hobson, 1974;Kulbicki et al, 2005;Longenecker, 2007;Pereira, Barros, Zemoi, & Ferreira, 2015;Randall, 1967;Ross, 1986;Talbot, Russell, & Anderson, 1978). Studies employing alternative strategies such as field observations of feeding behaviours (i.e., for corallivorous and herbivorous fish [Adam, Kelley, Ruttenberg, & Burkepile, 2015;Allgeier, Adam, & Burkepile, 2017;Pratchett, 2005Pratchett, , 2007Pratchett & Berumen, 2008]), or combinations of gut content and stable isotope analyses (Ho et al, 2007;Nagelkerken, van der Velde, Wartenbergh, Nugues, & Pratchett, 2009) have identified more pronounced dietary differences between co-occurring species.…”
mentioning
confidence: 99%